Association between Maternal Depressive Symptoms with Overweight/Obesity among Children Aged 0-5 Years According to the 2016 Demographic and Family Health Survey - Echevarría-Castro, Nataly (2020)
Background: Overweight and obesity among children under the age of 5 have become a public health problem. The worldwide prevalence is 4.9% and 6.0%, whereas in Peru it is 7.4% and 1.9%, respectively. The causes of these problems are multifactorial and must be studied to prevent the multiple consequences on children's health. Methods: Secondary data analysis of the 2016 Demographic and Family Health Survey (DHS). The sample size was 7935 children and their mothers. The dependent variable was childhood overweight/obesity, measured according to the Z-score of the BMI >2 standard deviation (SD), while the main independent variable consisted of the maternal depressive symptoms (DS) (Patient Health Questionnaire-9 score >10 points). The software STATA/MP 14.0 was used for statistical analysis. Results: The prevalence of overweight/obesity among children aged 0-5 years was 4.5% and the prevalence of moderate and severe maternal DS was 7.1%. No maternal depressive symptoms were found to be associated with the outcome [adjusted PR = 1.36 95% confidence interval (CI) = 0.59-3.09 p = 0.47]. An association was found between socioeconomic status (SES) Q3 (adjusted PR = 3.86 95% CI = 1.9-7.6 p < 0.0001), Q4 (adjusted PR = 5.53 95% CI = 2.76-11.1 p < 0.0001), Q5 (adjusted PR = 6.9 95% CI = 3.24-14.7 p = < 0.0001), maternal BMI (adjusted PR = 1.06 95% CI = 1.03-1.08 p < 0.0001), and cesarean delivery (adjusted PR = 1.42 95% CI = 1.01-1.99 p = 0.042). Conclusions: No association was found between maternal depressive symptoms and overweight/obesity among children aged 0-5 years. The upper SES quintiles, maternal BMI, and cesarean delivery were associated with the outcome.